New Polymers for Special Applications - De Souza Gomes, Ailton (IntechOpen, 2012)
This book comprises the contributions of several authors in the area of polymer physics by application of conducting polymers; hydrogel films on optical fiber core; thin film polymers; PDLC films application; photopolymers for holographic media; microwave absorption and EMI shielding behavior of nanocomposites based on intrinsically conducting polymers and graphene and carbon nanotubes; in the area of polymer synthesis of conducting polymers; oxidative polymerization of aniline; electro reductive polymerization; polysilanes with ordered sequences; radiation cross-linking poly(urethane-imide) and nitrogen-rich polymers as candidates for energetic applications; development of ruthenium complexes to novel functional nanocomposites. We hope that this book will help inspire readers to pursue study and research in this field.